Radicalism on teens as the effect of digital media usage - Suraya,; Mulyana, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research takes a deeper examination of the pattern of digital media consumption by teenagers. The consumption pattern is believed to give effects on particular teenagers. Youth lives in their time. The functions of social media, which were initially intended for connecting relations and sources of information, have shifted into a different meaning. In some cases, like on the Islamic digital media that publish the news about Islamic movements, such media is believed has the power to give the influence to shape its audience’s attitude into radicalism behavior. This study is facilitated by the Reasoned Action Theory, which was first introduced by Ajzen. This theory connects beliefs, attitudes, intentions, and behavior. This research is done through a survey of 100 senior high school students in Depok city, West Java, Indonesia. Data are being analyzed through the Pearson Correlation Product Moment and Simple Regression Analysis. The result shows a high rate of radicalism behavior by senior high school students in Depok city. The Influence of The frequency of digital media used on high school students appears to give a little contribution towards radicalism behavior. Meanwhile, the correlation between the frequency of digital media usage and the attitude of radicalism appears to be significantly weakened.